Hubungan antara Dukungan Sosial dengan Kesejahteraan Psikologis pada Driver Keluarga Gojek Serong - Aripin Ilham; Dwi Despina (Indonesian Journal of Behavioral Studies, 2021)
This study aims to determine the relationship between social support and psychological well-being of the serong gojek driver family. The research subjects were 65 driver of serong gojek driver family. Data collection using social support scale and psychological well-being scale. this research uses correlational quantitative method with Pearson’s product moment analysis. The results of the study revealed that there was a significant relationship between social support and psychological well-being in the Serong Gojek family drivers, this was evidenced by the correlation coefficient r = 0.896 (p <0.05), it means that the higher the social support, the higher the psychological well-being.